The RELATIONSHIP BETWEEN TYPES OF PLASMODIUM FALCIPARUM AND PLASMODIUM VIVAX WITH THE DEGREE OF THROMBOCYTOPENIA IN MALARIA PATIENTS AT RSUD RATU AJI PUTRI BOTUNG PENAJAM PASER UTARA - Doni Suryadi; Vera Madonna Lumban Toruan; Fransiska Anggreni Sihotang; Loly Rotua Dharmanita Siagian (Universitas Muhammadiyah Kalimantan Timur, 2021)
Malaria is a tropical infectious disease with high morbidity and mortality rates. In malaria, various kinds of haematological complications can arise, one of which is thrombocytopenia. Thrombocytopenia is most commonly encountered during acute malaria infection with varying degrees observed in both Plasmodium falciparum and Plasmodium vivax infections. The purpose of this study was to determine the relationship between the types of Plasmodium falciparum and Plasmodium vivax with the degree of thrombocytopenia in malaria patients at the Ratu Aji Putri Botung Penajam Paser Utara Hospital. This research is an observasional analytic study with cross sectional method. The data was taken by using purposive sampling method from the medical records of malaria patients hospitalized in Ratu Aji Putri Botung Penajam Paser Utara Hospital in the period of January 2013 - August 2018. Data analysis used the Chi-square test. Of the 310 malaria patients who were study subjects, 60,3% (n = 187) were infected with Plasmodium falciparum and 39,7% (n = 123) were infected with Plasmodium vivax. Most of the research subjects were male (95,8%) who were dominated by adults (56,5%). As many as 90% of malaria patients experienced thrombocytopenia with mild, moderate, and severe thrombocytopenia respectively 29,4% ; 56,6% ; 14,0%. Severe thrombocytopenia was more common in falciparum malaria patients (16,4%). The statistical test result for the type of Plasmodium with the degree of thrombocytopenia were p = 0,139. It was concluded that there was no relationship between the types of Plasmodium falciparum and Plasmodium vivax with the degree of thrombocytopenia in malaria patients.